CRESCIMENTO ECONÔMICO, DESMATAMENTO E EMISSÕES DE GASES DE EFEITO ESTUFA: ANÁLISES PROSPECTIVAS PARA OS BIOMAS BRASILEIROS NUMA PERSPECTIVA DE SUSTENTABILIDADE - Gessica Cardoso Pereira de Souza (2022)
Brazil is a major agricultural producer and exporter, with agribusiness accounting for 26.6% of the country's GDP. The growth of agriculture and livestock is the result of increased agricultural productivity and expansion over native vegetation. It is estimated that in 33 years, the country lost 102 million hectares of natural vegetation, mainly in the Amazon and Cerrado biomes. This value is equivalent to 3.1 Mha or 166 thousand Maracanã stadiums per year. Deforestation causes direct and indirect changes in land use and an increase in gross greenhouse gas (GHG) emissions. The impacts of the increase in GHGs and climate change are diverse and are not limited to the environmental sphere alone. Brazil has ambitious GHG mitigation and deforestation reduction targets, facing a possible trade off between environmental conservation and economic growth. In this sense, the main objective of this thesis is to simulate a scenario of economic growth with forest preservation, called “Green Growth”. In this scenario, deforestation for productive purposes is zeroed and sectoral investments are intensified. The secondary objective is to investigate the impacts of the zero deforestation policy occurring together with the recovery of degraded areas, one of the Brazilian mitigation goals. A Computable General Equilibrium (CGE) model was built for the analysis in question. BLUME incorporates a land use module capable of capturing the processes of direct and indirect land use changes integrated into an emissions module capable of projecting emissions not only from land use changes, but also from other emitting sectors. The model is regionalized according to Brazilian states and biomes, allowing the capture of regional heterogeneity at the environmental and land use levels. The results indicate that the policies simulated in this thesis would be able to avoid part of deforestation and national emissions, maintaining the country's economic growth at a relatively small cost compared to the national GDP. Therefore, there is indeed a trade off between economic growth and deforestation, but this trade off is small and would be easily reversed with targeted investments. In addition, policies to restrict deforestation in the two largest Brazilian biomes (Amazon and Cerrado) are more efficient from an environmental point of view. The livestock sectors would need differentiated investments and economic stimuli to be able to reconcile economic growth and forest preservation. Finally, the emission targets defined during COP21 for 2025 could be achieved with zero deforestation in the Amazon and Cerrado and with the reforestation of 12 Mha at a relatively low cost, compared to the GDP of the regions.